Metode Role Play Sebagai Upaya Meningkatkan Kemampuan Guru dalam Deteksi Dini Pertumbuhan Perkembangan Balita - Nurwening Tyas Wisnu; Ayesha Hendriana Ngestiningrum; Nuryani Nuryani; Hery Sumasto (FORIKES, 2020)
Several studies have shown that the role of elementary school, kindergarten and PAUD (Early Childhood Education) teachers in early detection of toddler growth and development is very important in efforts to monitor and detect early childhood growth and development. This study aims to analyze the influence of role play learning methods using MCH books to improve the ability of teachers to detect children's growth and development. The design of this study was static group comparison. The study subjects were 100 PAUD Teachers in Poncol District, Magetan Regency, which were divided into treatment and control groups. Data was collected through questionnaires and observations using a checklist. Differences in the ability to detect growth and development of children between the two groups were analyzed using the t test. The results of data analysis show that there was an influence of the use of role play on the ability to detect growth, development and mental emotional problems in children. Keywords: children; growth; development, mental-emotional, role play; teacher ABSTRAK Beberapa penelitian menunjukkan bahwa peran guru SD, TK dan PAUD (Pendidikan Anak Usia Dini) dalam deteksi dini tumbuh kembang Balita sangat penting dalam upaya pemantauan dan deteksi dini tumbuh kembang balita. Penelitian ini bertujuan untuk menganalisis pengaruh metode pembelajaran role play penggunaan buku KIA untuk meningkatkan kemampuan guru untuk mendeteksi pertumbuhan dan perkembangan anak. Desain penelitian ini adalah static group comparison. Subyek penelitian adalah 100 Guru PAUD di Kecamatan Poncol, Kabupaten Magetan, yang dibagi menjadi kelompok perlakuan dan kelompok kontrol. Data dikumpulkan melalui pengisian kuesioner dan observasi menggunakan checklist. Perbedaan kemampuan deteksi pertumbuhan dan perkembangan anak antara kedua kelompok dianalisis menggunakan uji t. Hasil analisis data menunjukkan bahwa ada pengaruh penggunaan role play terhadap kemampuan deteksi pertumbuhan, perkembangan dan masalah mental emosional pada anak. Kata kunci: anak; pertumbuhan; perkembangan, mental-emosional, role play; guru